HOMESTAY TOURISM: FROM THE DISTANT PAST UP TO PRESENT - Yasami, Mehri; Awang, Khairil; Teoh, Kenny (PEOPLE: International Journal of Social Sciences, 2017)
While homestay tourism as an effective catalyst for socio-economic development in the rural areas has been widely discussed in the tourism literature, very few studies have investigated the historic roots and evolutionary path of the homestay. This study conducted a thorough review of homestay history in order to explain what factor gave rise to the homestay tourism and what significant forces in the modern society have shaped the contemporary homestay tourism. This paper shows that the business of homestay, from its earliest days as in the past shares the characteristics of the homestay tourism as we know it today. It also acknowledges how homestay tourism has evolved through societies’ religious beliefs, financial incentives, and nobles’ hunger for novel cultural experience, environmental awareness, enhanced demands for solitude, poverty reduction, and sustainable tourism development over centuries. Furthermore, it clarifies that the modern tourists consider homestay as an alternative lodging experience to the normal chain hotels due to its capability in creating a short relaxing break in a homelike atmosphere allowing them to experience host culture and pristine nature in more authentic way.